História evolutiva dos elementos homo1 e howilli2 de espécies de drosofilídeos neotropicais - Bernardo, Larissa Paim (2013)
Transposable elements (TEs) are DNA fragments that can move within and between genomes causing great impact on the evolution of organisms. The hAT superfamily belongs to class II, subclass I of TEs and despite having originally been described in insects and plants, it is now known that these elements have a wide distribution and are diverse in many groups of higher organisms. Phylogenetic studies show that this superfamily is very ancient and its occurrence in these groups may be related to events of horizontal transfer (HT). This work was performed in order to estimate possible cases of hATs elements' HT. The elements homo1 and howilli2 described by Ortiz and Loreto in 2009 in D. willistoni and D. mojavensis species were searched in Neotropical Drosophila genomes using PCR with degenerate primers and because they are very similar elements and described in distantly related species, it was suggested that these elements might be being transmitted horizontally. Amplification was detected in 18 of the 34 species analyzed and these elements showed a patch distribution and incongruities with the TEs and host species' phylogeny, suggesting possible cases of HT. In addition, the estimated divergence of sequences found showed that these elements are or recently were active in the genomes that were investigated. Thus, our results demonstrate that these elements could be in an expansion process in Neotropical drosophilid genomes due to the large amount of HT events observed.